Chemical Diversity of Sands Within the Linear and Barchan Dunes of the Bagnold Dunes, Gale Crater, as Revealed by APXS Onboard Curiosity. Issue 18 (23rd September 2018) - O'Connell‐Cooper, C. D.; Thompson, L. M.; Spray, J. G.; Berger, J. A.; VanBommel, S. J.; Gellert, R.; Boyd, N. I.; DeSouza, E.
Abstract: Alpha Particle X‐ray Spectrometer (APXS) results for Phase 2 of the Bagnold Dunes campaign, focusing on the linear dunes, complement those from Phase 1 (barchan dunes) and add to our understanding of active Martian dune systems. This work highlights both compositional similarities and differences across the dune field. The concentration of elements associated with mafic minerals in coarser grains and along active ripple crests, previously identified in the barchan dunes, highlights differences in Martian and terrestrial weathering, transport, and sorting processes. Concentration of a Cr‐Ti mineral phase within the linear sands is identified. The inactive ripple fields are geochemically similar to soil, while active ripple fields are similar to sands. Inferred dust content (S + Cl + Zn concentrations), derived from APXS analyses, provide geochemical confirmation of current and seasonal activity variations, within the barchan and linear dunes, as well as revealing a continuum between inactive soils and active sands. Plain Language Summary: During 2015–2017, the Mars Science Laboratory rover, Curiosity, in Gale Crater, Mars, crossed the active Bagnold Dunes, which comprise both barchan (crescent shaped) and linear dunes. This has enabled the first in situ appraisal of an active dune system on another planet, including the geochemical analysis (major elements, plus Ni, Zn, and Br) of sand samples via the Alpha Particle X‐ray Spectrometer. We find a concentration of elements (MgO and Ni) associated with mafic minerals (particularly olivine) along the crests of active ripples and in coarse‐grained samples. Elements such as SiO2, Al2 O3, and K2 O, associated with more felsic minerals such as plagioclase, are concentrated in off‐crest sand and finer‐grained portions. We find evidence for a Cr2 O3 ‐TiO2 mineral phase, concentrated in the linear dunes. Dust content (indicated by SO3, Cl, and Zn levels) indicates that activity levels are higher in the linear dunes than in the barchan dunes. Key Points: Alpha Particle X‐ray Spectrometer results reveal compositional similarity between basaltic Bagnold barchan and linear sands (Gale Crater) Evidence of mineral segregation, and mafic element concentration in coarser fractions, along active ripple crests is observed Linear sands show evidence for the concentration of a Cr‐Ti mineral phase, previously undetected in the barchan dunes